1979
DOI: 10.1007/bf01297237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol on plasma protein shedding in the human stomach

Abstract: Plasma protein shedding in the stomach was measured in 23 normal individuals before and after intragastric administration of a 30% solution of ethyl alcohol. Two different methods were used to assess plasma protein shedding. The first technique utilizes [131I]albumin and requires neutralization of the gastric juice. It was used in 12 subjects and failed to demonstrate any increase of plasma protein shedding under the influence of ethanol. The second technique which utilizes [51Cr]chloride was used in 11 subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Free radicals created by HCl-ethanol injury are thought to attack the protein which might lead to a reduction in the protein levels [31]. It has also been reported that ulcerative lesions of the gastrointestinal tract may be associated with increased loss of protein [42], and this was also observed in our study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Free radicals created by HCl-ethanol injury are thought to attack the protein which might lead to a reduction in the protein levels [31]. It has also been reported that ulcerative lesions of the gastrointestinal tract may be associated with increased loss of protein [42], and this was also observed in our study.…”
Section: Discussionsupporting
confidence: 85%
“…It was reported that ethanol and bile salts had similar effects [41]. Other supporting evidence is that alcohol increases the loss of protein into the gastric content in the presence of HC1 [42].…”
Section: Discussionmentioning
confidence: 84%
“…The mucosal proteins are easily susceptible to oxidative free radicals produced by HCl±ethanol, resulting in corrosion, disruption and disintegration of mucosal cells (Davenport 1967;Guth et al 1984). Alcohol intake is reported to increase the loss of mucosal proteins into the gastric juice in the presence of HCl (Brossinne 1979). Increased loss of protein in the ulcerated condition might be a major factor involved in the induction of ulcerative lesions of the gastrointestinal tract.…”
Section: Groupsmentioning
confidence: 99%
“…The leakage or transudation of plasma from microcapillaries into interstitial spaces, and then into the lumen of the stomach, is a normal occurrence (Brassinne, 1979;Hollander & Horowitz, 1962), and is increased considerably when gastric mucosa is damaged experimentally (Brassinne, 1979;Sober et al, 1950) or through disease (Brassinne, 1974;Jarnum & Jensen, 1972). Thus, H. pylori colonizing the gastric microenvironment will be exposed to plasma, and Abbreviations: CLV, curvilinear velocity; CR, chemotactic response.…”
Section: Introductionmentioning
confidence: 99%